2023
DOI: 10.1111/nzg.12348
|View full text |Cite
|
Sign up to set email alerts
|

Emerging transitions in organic waste infrastructure in Aotearoa New Zealand

Abstract: Aotearoa New Zealand is at a critical juncture in reducing and managing organic waste. Research has highlighted the significant proportion of organic waste sent to landfills and associated adverse effects such as greenhouse gas emissions and loss of valuable organic matter. There is current debate about what practices and infrastructure to invest in to better manage and use organic waste. We highlight the diversity of existing organic waste practices and infrastructures, focusing on Auckland, Wellington and Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Finally, the findings indicated that infrastructural and institutional barriers hinder the sustainable development efforts of the FP companies, including inadequate waste management infrastructure, a lack of environmental regulations for air emissions and limited recycling facilities (Diprose et al , 2023; Sustainable Business Network, 2021). In addition, the missing recycling labels on plastic packaging products also create infrastructural barriers preventing the FP industry from achieving sustainable development; nevertheless, there is a lack of studies highlighting this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the findings indicated that infrastructural and institutional barriers hinder the sustainable development efforts of the FP companies, including inadequate waste management infrastructure, a lack of environmental regulations for air emissions and limited recycling facilities (Diprose et al , 2023; Sustainable Business Network, 2021). In addition, the missing recycling labels on plastic packaging products also create infrastructural barriers preventing the FP industry from achieving sustainable development; nevertheless, there is a lack of studies highlighting this issue.…”
Section: Discussionmentioning
confidence: 99%
“…According to an estimate, the daily plastic waste per capita [grams(g)/person/day] in NZ is approximately 159 g, compared with larger populous countries like Australia with 117 g per person, and Norway with only 26 g per person (De Bhowmick et al , 2021). Furthermore, NZ is also facing several sustainability problems such as increasing landfill, lack of recycling infrastructure and increasing food waste associated with the FP industry (Diprose et al , 2023; Farrukh et al , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…These are all social as well as ecological problems. The kinds of infrastructures that separate us from the cycling of organic waste/nutrients produce a particular kind of waste subjectivity (Diprose et al, 2023). The kind of thinking that focuses on separations, categories, hierarchies and classifications both emerges from and contributes to forms of relational metabolic rift.…”
Section: Metabolic Rifts In the 21st Centurymentioning
confidence: 99%
“…Street food pantries provide a means through which responsibility for the provisioning of food is localised, in that it shifts from food banks to local communities and individuals who are in need (Diprose et al, 2023). A focus on street food pantries, then, goes beyond the material circulation and redistribution of food itself, in order to understand the blurring of home and paid work and gendered suburban geographies of responsibility (Strong, 2020).…”
Section: Introductionmentioning
confidence: 99%